Customer relationship management / Wan Kalthom Yahya and Sharifah Zannierah Syed Marzuki - Yahya, Wan Kalthom; Syed Marzuki, Sharifah Zannierah (2004)
With today's dynamic global market scenario, it is a requirement for company to improve interaction with the customer in order to retain, win and also to keep them. It is easy to retain existing customer that will become the loyal customer rather than to find new customer. Customer Relationship Management (CRM) is an integrated approach in managing relationship by focusing on customer retention and relationship management. Optimizing customer relationship requires a complete understanding of all customers as well as non-profitable; and then to organize business process to treat customers individually on their needs and values. Therefore, to manage a successful CRM implementation, a balanced and integrated approach to technology, process and people is a requirement.